2021
DOI: 10.3390/nu13051499
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of COVID-19 Pandemic on Eating and Purchasing Behaviours of People Living in England

Abstract: Consumers’ eating habits have changed significantly due to the anxiety and boredom from the reported cases and deaths of COVID-19, the change in work patterns, controlled food shopping, and the inability to meet loved ones during the lockdown. The magnitude of these changes in the eating behaviours and purchasing habits of consumers varies across different groups of people. This study provides empirical evidence of the effects of COVID-19 on the eating and purchasing behaviours of people living in England, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 32 publications
(36 reference statements)
0
34
0
Order By: Relevance
“…For instance, larger households, especially families with children, tend to stockpile more food than smaller ones. Indeed, the consequences of COVID-19 on the economy, health, well-being, and nutrition varied not only from a household to another but also among individuals [79]. Overall, COVID-19 s effect on consumer behavior has been shaped by many factors, including sociodemographic and household preferences and attitudes [80].…”
Section: Effects Of Sociodemographic Characteristics On the Stockpili...mentioning
confidence: 99%
“…For instance, larger households, especially families with children, tend to stockpile more food than smaller ones. Indeed, the consequences of COVID-19 on the economy, health, well-being, and nutrition varied not only from a household to another but also among individuals [79]. Overall, COVID-19 s effect on consumer behavior has been shaped by many factors, including sociodemographic and household preferences and attitudes [80].…”
Section: Effects Of Sociodemographic Characteristics On the Stockpili...mentioning
confidence: 99%
“…However, studies to date assessing the influence of COVID-19 lockdown restrictions on dietary behaviours in UK adults have largely been cross-sectional and undertaken during the initial months of lockdown ( 7 , 14 , 19 ). Some cross-sectional analyses show dietary changes during August–October 2020 compared to the pre-pandemic period ( 1 , 30 , 31 ), and changes in consumer habits during November–December 2020 ( 10 ). Herle et al identified multiple eating trajectories of UK adults during the initial months of the pandemic, including individuals with an initial increase in eating at the start of the pandemic, followed by a gradual return to pre-pandemic food intake by May 2020 ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Silva et al (2021) and Salman et al (2021) also noted an increase in the consumption of vegetables and fruits during the pandemic [49,50]. It is worth noting that the elderly during the pandemic were characterized by a greater decrease in healthy food consumption than the younger generations [51]. Increased consumption of carbohydrate sources has also been noted in other studies [19,20,45].…”
Section: Discussionmentioning
confidence: 56%